Development of rational bioprocess design strategies for a clinically relevant protein candidate - Anindya Basu (2012)
The Hepatitis B Virus X (HBx) protein has been associated with the initiation and development of hepatocellular carcinoma (HCC), a killer disease affecting millions of lives worldwide. Being a multifunctional viral regulator, the HBx protein has been found to modulate all major host cellular metabolic pathways, causing scientists to hypothesize that it can be a potential drug target for the disease. However, the HBx protein is expressed at very low levels within the infected host cells. Increase in HBx yield can be achieved by recombinant production in bacteria host systems but this often results in the insoluble expression of the protein. The lack of pure bioactive HBx continues to hinder research progress to study the protein’s structure-function and hence the development of new anti-HBx drug candidates. Moreover, the absence of native HBx also prevents quantitative bioactivity determination of the protein, making bioprocess design and scale-up studies difficult to perform. To overcome this roadblock, my research project aims to develop a scalable bioprocess for HBx production at amounts that are sufficient for subsequent structural characterisation and drug designing studies. HBx expression and bioprocess development studies commenced with the use of a glutathione S transferase (GST) tagged HBx construct. The use of this construct, however, was challenged by inefficient Factor Xa cleavage and poor economics. Thereafter, a new 6His-HBx protein construct was designed which only comprised a 6-histidine (His)tag to ease recovery of the protein using immobilised metal affinity chromatography (IMAC). As the 6His-HBx protein was expressed as insoluble inclusion bodies (IBs), rational strategies employing second virial coefficient (SVC) measurements in combination with a Statistical design of experiments (DoE) platform were developed to facilitate rapid determination of optimal physicochemical conditions necessary to retain HBx solubility and stability. The SVC studies clearly indicated the importance of a net reducing environment combined with L-arginine (an aggregation inhibitor) for improved solubility of HBx, a highly hydrophobic protein with 9 cysteine residues. The SVC results guided the rational design of a HBx refolding buffer to maintain HBx in a stable soluble state, leading to the development of a dilution refolding based bioprocess for HBx. Further improvement of the process was impeded by the absence of an analytical platform to evaluate HBx refolding yields. To overcome this roadblock, a novel ELISA platform for HBx was subsequently developed to quantitatively determine HBx refolding yields.